Implementation Of Best Practices In Islamic Religious Education At State Vocational High School Labuhanbatu District - Ahmad Syawaluddin, Fauzi; Nahar, Syamsu; Usiono, Usiono (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze best practice planning for Islamic Religious Education, analyze the implementation of best practice Islamic Religious Education, analyze barriers to implementing best practice Islamic Religious Education, and analyze efforts to overcome barriers to implementing best practice Islamic Religious Education at State Vocational Schools in Labuhanbatu Regency.This research method is a qualitative research method with a phenomenological research approach. This research was carried out to build knowledge through understanding and discovery based on a methodology that investigates a phenomenon and problem. The data collection techniques used were observation, interviews, documentation studies. Data management consists of data reduction, data display/data presentation, data analysis, drawing conclusions for research results.The results of research on best practice planning for Islamic Religious Education at Rantau Utara State Vocational School, Labuhanbatu Regency include curriculum development, development of innovative and interactive teaching methods, training and development of teacher competency, and facilities and infrastructure.Implementation of best practice Islamic Religious Education at Rantau Utara State Vocational School, Labuhanbatu Regency, namely implementing learning with curriculum innovation, IT-based learning innovation, practical media-based learning innovation, and extracurricular supporting activities. In particular, extracurricular activities are further developed through several activities such as tahsin, tahfiz, Islamic Holiday Commemoration activities, and Islamic art.